Volume 10 Number 4 2014
DOI: 10.18057/ijasc.2014.10.4.7
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Fatigue Behavior of Welded CFCHS T-Joints

Abstract: Fatigue life assessment of welded joints made of circular hollow sections (CHS) with concrete filled (CF) chord member subject to vehicle load is vital in designing of CFCHS arch truss bridge. A key issue in fatigue life assessment of such joints is how to accurately estimate the stress intensity factor. This paper describes a methodology for calculating the stress intensity factor of the hot spot region in the welded CFCHS T-joints based on a finite element analysis which considers weld modeling, crack modeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Fang et al [20] simulated crack propagation direction and path in a perforated plate using Abaqus, with results closely aligning with experimental data. In another study, Gu et al [21] calculated the stress intensity factor (SIF) of cold-formed, circular, hollow-section (CFCHS), T-type, welded joints using Ansys software and developed a method for assessing the fatigue life of such joints. The extended finite element method (XFEM) is the most prevalent technique for investigating fatigue crack propagation issues.…”
Section: Introductionmentioning
confidence: 99%
“…Fang et al [20] simulated crack propagation direction and path in a perforated plate using Abaqus, with results closely aligning with experimental data. In another study, Gu et al [21] calculated the stress intensity factor (SIF) of cold-formed, circular, hollow-section (CFCHS), T-type, welded joints using Ansys software and developed a method for assessing the fatigue life of such joints. The extended finite element method (XFEM) is the most prevalent technique for investigating fatigue crack propagation issues.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to observe in reference [5] the design of welded tubular connections. Fatigue is an important issue in designing welded joints [6]. That paper presented a fracture mechanics approach to assess the fatigue life of CFCHS T-joints, which involves the determination of initial crack location and size, stress intensity factor and proper crack growth model (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…That paper presented a fracture mechanics approach to assess the fatigue life of CFCHS T-joints, which involves the determination of initial crack location and size, stress intensity factor and proper crack growth model (Figure 2). In [6], numerical and experimental analyses on welded joints were presented. Figure 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al [3] monitored the structural behavior of a 25 m span simply-supported RC girder bridge in China on basis of the in-situ traffic survey data and found that the maximum stress in the longitudinal reinforcement may reach up to about 85% of its yield strength. Usually the vehicle overloading does not cause an RC bridge to collapse instantly, but the high stress amplitude caused by overloading will definitely accelerate the damage accumulation and the structural performance degradation in critical details [4]. In both USA and China, Hersi [5], Ji and Fu [6] found that vehicle overloading has become a major factor leading to the failure of bridge structures (Figure1 and Figure 2).…”
Section: Introductionmentioning
confidence: 99%